Differential effects of TRPM4 channel inhibitors on Guinea pig urinary bladder smooth muscle excitability and contractility: Novel 4‐chloro‐2‐[2‐(2‐chloro‐phenoxy)‐acetylamino]‐benzoic acid (CBA) versus classical 9‐phenanthrol - John Malysz; Sarah E. Maxwell; Georgi V. Petkov (Wiley, 2022)
Abstract Non‐selective cation channels in urinary bladder smooth muscle (UBSM) are thought to mediate increases in cellular excitability and contractility. For transient receptor potential melastatin type‐4 (TRPM4) channels, the evidence primarily relies on the inhibitor 9‐phenanthrol, which exhibits pharmacological limitations. Recently, 4‐chloro‐2‐[2‐(2‐chloro‐phenoxy)‐acetylamino]‐benzoic acid (CBA) has been discovered as a novel TRPM4 channel blocker. We examined how, in comparison to 9‐phenanthrol, CBA affects the excitability of freshly isolated guinea pig UBSM cells and the contractility of UBSM strips. Additionally, non‐selective TRPM4 channel inhibitor flufenamic acid (FFA) and potentiator BTP2 (also known as YM‐58483) were studied in UBSM cells. Unlike robust inhibition for 9‐phenanthrol already known, CBA (up to 100 μM) displayed either no or a very weak reduction (<20%) in spontaneous phasic, 20 mM KCl‐induced, and electrical field stimulated contractions. For 300 μM CBA, reductions were higher except for an increase in the frequency of KCl‐induced contractions. In UBSM cells, examined under amphotericin B‐perforated patch‐clamp, CBA (30 μM) did not affect the membrane potential (I = 0) or voltage step‐induced whole‐cell cation currents, sensitive to 9‐phenanthrol. The currents were not inhibited by FFA (100 μM), increased by BTP2 (10 μM), nor enhanced under a strongly depolarizing holding voltage of −16 or + 6 mV (vs. −74 mV). None of the three compounds affected the cell capacitance, unlike 9‐phenanthrol. In summary, the novel inhibitor CBA and nonselective FFA did not mimic the inhibitory properties of 9‐phenanthrol on UBSM function. These results suggest that TRPM4 channels, although expressed in UBSM, play a distinct role rather than direct regulation of excitability and contractility.